2021
DOI: 10.1155/2021/5513817
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Sleep and Mental Health among Saudi Adolescents

Abstract: Among adolescents, mental health issues (i.e., stress and depressive symptoms) negatively affect sleep. We assessed whether the association between mental health and sleep varied between genders among Saudi adolescents. A total of 2206 school students (grades 7-12) from 40 randomly selected schools in four cities of Al-Qassim province in Saudi Arabia participated in this cross-sectional study. The survey assessed demography, lifestyle, sleep (12-item Medical Outcomes Study Sleep Scale), depression (Depression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…Given the number of studies demonstrating the adverse effects of insufficient sleep on adolescents’ and young adults’ physical and mental health, the increasing proportion of those who do not get the recommended hours of sleep raises public health concerns. On the other hand, a large body of literature has shown that adolescent and young females suffer more frequently from sleep disorders than males [ 36 38 ], and the current study has supported this suggesting a call for special attention for the development of gender-based initiatives by health-decision makers and policy experts in the country. Excessive screen exposure in some studies was shown to be associated with poor psychosocial well-being, and sleep played a mediating role [ 39 ].…”
Section: Discussionsupporting
confidence: 71%
“…Given the number of studies demonstrating the adverse effects of insufficient sleep on adolescents’ and young adults’ physical and mental health, the increasing proportion of those who do not get the recommended hours of sleep raises public health concerns. On the other hand, a large body of literature has shown that adolescent and young females suffer more frequently from sleep disorders than males [ 36 38 ], and the current study has supported this suggesting a call for special attention for the development of gender-based initiatives by health-decision makers and policy experts in the country. Excessive screen exposure in some studies was shown to be associated with poor psychosocial well-being, and sleep played a mediating role [ 39 ].…”
Section: Discussionsupporting
confidence: 71%
“…The findings revealed that male students exhibited better mental health, sleep hygiene, and sleep quality, while female students had lower levels. The results are consistent with previous research that reported that male college students exhibited higher levels of positive mental health than female college students (Rajab et al, 2021). In addition, research has also found that male college students may engage in better sleep hygiene practices than female college students (Lund et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Other findings showed female adolescents experienced higher stress levels than males, in line with the study by Rajab et al (2021). It may be because females reported more frequent worries about their schoolwork and education during the pandemic (Lessard & Puhl, 2021).…”
Section: Discussionsupporting
confidence: 79%